2011
DOI: 10.3748/wjg.v17.i10.1336
|View full text |Cite
|
Sign up to set email alerts
|

Non-sequential narrow band imaging for targeted biopsy and monitoring of gastric intestinal metaplasia

Abstract: AIM:To evaluate the efficacy of non-sequential narrow band imaging (NBI) for a better recognition of gastric intestinal metaplasia (GIM). METHODS:Previously diagnosed GIM patients underwent targeted biopsy from areas with and without GIM, as indicated by NBI, twice at an interval of 1 year. The authors compared the endoscopic criteria such as light blue crest (LBC), villous pattern (VP), and large long crest (LLC) with standard histology. The results from two surveillance endoscopies were compared with histolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
3
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 20 publications
0
42
3
1
Order By: Relevance
“…One study included in our meta-analysis followed 26/38 patients at 1-year intervals, and found that LBC under NBI-ME can be used effectively to surveil gastric IM, but did not find the optimal duration of follow-up [17]. The first European Guidelines on management of precancerous conditions and lesions in the stomach recommended that patients with extensive atrophic gastritis (AG) and/or extensive IM should be offered endoscopic surveillance every 3 years [25].…”
Section: Discussionmentioning
confidence: 98%
“…One study included in our meta-analysis followed 26/38 patients at 1-year intervals, and found that LBC under NBI-ME can be used effectively to surveil gastric IM, but did not find the optimal duration of follow-up [17]. The first European Guidelines on management of precancerous conditions and lesions in the stomach recommended that patients with extensive atrophic gastritis (AG) and/or extensive IM should be offered endoscopic surveillance every 3 years [25].…”
Section: Discussionmentioning
confidence: 98%
“…One study used NBI for targeted biopsy and surveillance of gastric IM and reported that the sensitivity and specificity of first/second surveillances are 78.8%/91.3% and 82.5%/89.1%, respectively 33. Similarly, another study reported that NBI increases the diagnostic yield for the detection of IM and dysplasia, and showed that the sensitivity and specificity of NBI were 71% and 58%, respectively 34.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the sensitivities of each criterion for GIM diagnosis are variously suboptimal and have not been well standardized. For instance, LBC provided only 70% in sensitivity, whereas VP showed a lower sensitivity at 30% . Therefore, a combination of criteria are required to improve the sensitivity; however, this in turn may result in a lower specificity .…”
Section: Discussionmentioning
confidence: 99%
“…Over the last decade, digital chromoendoscopy (DC), including narrow band imaging (NBI), i‐scan, and flexible spectral imaging color enhancement (FICE), has been developed to diagnose EGC. Although the accuracies (70–95%) of DC for EGC and GIM detection are comparable, the interobserver agreement for GIM detection using DC remains suboptimal (κ = 0.49) . Moreover, a certain length of training is necessary for inexperienced endoscopists .…”
Section: Introductionmentioning
confidence: 99%